Geographical and Ecological study of some Species of Tribe Cardueae in Middle and North of Iraq - Ayman Adwan Abd; Rawad Khalaf Hameed; Hisham Majeed Shlash (Tikrit Journal of Pure Science, 2023)
The study of the environment and geographical distribution of several species of the Cardueae tribe in middle and northern Iraq was the focus of the current investigation. The study involved doing a field survey of a several Iraqi districts to determine new areas where the Cardueae tribe species might spread. As well as, the flowering period of the examined species was identified. The findings demonstrate the studied species' spread in north, north-east, and western regions. The more widespread and tolerant of varied environmental conditions was the species Silybum marianum L., and the least prevalent of the studied species was Carduus getulus Pomel., whereas the other species were relatively common in the study area. Maps of the geographic distribution of all species under study were also created.